The rare Holsteinian (Mazovian) interglacial limnic deposits in the Książnica outcrop at Krzczonów (near Świdnica), Sudetic Foreland. (15th January 2019) - Krzyszkowski, Dariusz; Wachecka-Kotkowska, Lucyna; Malkiewicz, Małgorzata; Jary, Zdzisław; Tomaszewska, Klara; Niska, Monika; Myśkow, Elżbieta; Raczyk, Jerzy; Drzewicki, Wojciech; Hamryszczak, Dawid; Nawrocki, Jerzy; Ciszek, Dariusz; et al.
Abstract: The article presents the results of research on peats, muds and sands filling a palaeocavity within alluvial fans of the Bystrzyca River valley, in the Sudetic Foreland of SW Poland. In the 534-cm deep research profile in the central part of a palaeolake, 267 samples were collected at an interval of 2 cm and lithologically (structural and textural studies), palaeobotanically (studies of diatoms, pollen plant macrofossils and fossil wood), palaeozoologically (Cladocera, Mollusca and Ostracoda), geochemically (chemical elements and isotopes) and palaeomagnetically analyzed. The profile consists of three parts: organic with mineral layers (lower), mineral (middle), and organic (upper). The palynological diagram was divided into three zones that represent local sets of pollen zones. This diagram, although incomplete, is clearly indicative of the younger part of the Holsteinian (Mazovian: pollen III and IV periods interglacial). The upper part of the diagram consists of four local pollen zones that are correlated with stadial and interstadial periods. Analysis of several samples of fossil wood shows the widespread presence of Pinus remains and numerous fragments of rhytidome (bark) of Betula . Development of the peat layer (1.36–0.68 m depth) started with paludification of the forest with the Betula forest. Analysis of Cladocera shows the presence of chitin armor components (species: Chydorus sphaericus, Alona rectangula and ephippia of Alona rectangula ) in three samples. Lithological, Cladocera and palaeo-magnetic research, supported by geochemical studies, indicate the existence of at least three main phases. The lake originated during the younger part of the Holsteinian (Mazovian) Intergalcial as an oxbow within the valley, where the deposition of variously thick (up to 1.5 m depth) peats, organic and minerogenic silts (the first stage). In the second phase, a closed, fairly deep late Holsteinian lake continued to exist under relatively warm conditions with mainly mineral deposition from the slope. The lake became shallower and wider, and then more open and better oxygenated (with through-flow). In the final phase the lake was completely filled by organic sediments under interglacial conditions. The absence of diatom, molluscan and ostracod communities indicates an acid lacustrine environment at this time. The fluvial and limnic deposits are sealed by overlaying Saalian (Odranian) till.